Odpowiedź :
Odpowiedź:
A)=2x² - 10x - 3x² +6x +x² - 2x=6x
B)=a²+ab+ac-ab+b²-bc-ac+bc+c²=a²+b²+c²
C)=3x³-2x²+x+3
D)=4b²-2b
Szczegółowe wyjaśnienie:
Liczbę znajdujące się przed nawiasem mnożymy przez każdy wyraz znajdujący się w nawiasie
Odpowiedź:
a)
3x(x - 5) - 3(x² - 2x) + (x - 2)x = 3x² - 15x - 3x² + 6x + x² - 2x = x² - 11x
b)
a(a + b + c) - b(a - b + c) - c(a - b - c) = a² + ab + ac - ab + b² - bc - ac + bc + c² =
= a² + b² + c²
c)
x(x² + 2x + 1) - (-4x³ + 8x² - 6) : 2 = x³ + 2x² + x + 2x³ - 4x² + 3 = 3x³ - 2x² + x + 3
d)
12b * (b - 1)/4 + 14* (b² - 2b)/21 - (b - b²)/3 = 3b² - 3b + 2/3b² - 4/3b - 1/3b + 1/3b² = 4b²- 3b - 5/3b = 4b² - 1 2/3b
= 4b² - 2b
Szczegółowe wyjaśnienie: